2017
DOI: 10.1038/s41467-017-01948-9
|View full text |Cite
|
Sign up to set email alerts
|

Dendrogenin A drives LXR to trigger lethal autophagy in cancers

Abstract: Dendrogenin A (DDA) is a newly discovered cholesterol metabolite with tumor suppressor properties. Here, we explored its efficacy and mechanism of cell death in melanoma and acute myeloid leukemia (AML). We found that DDA induced lethal autophagy in vitro and in vivo, including primary AML patient samples, independently of melanoma Braf status or AML molecular and cytogenetic classifications. DDA is a partial agonist on liver-X-receptor (LXR) increasing Nur77, Nor1, and LC3 expression leading to autolysosome f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
115
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(117 citation statements)
references
References 66 publications
(85 reference statements)
2
115
0
Order By: Relevance
“…Although the most convincing observations of ACD have been made using lower model organisms like Caenorhabditis elegans, Drosophila melanogaster, and Dyctiostelium discoideum [5,[11][12][13], numerous studies have also demonstrated bona fide ACD in mammalian cells [14][15][16][17][18][19]. Liu et al observed that a cell-permeable Tat-Beclin 1 peptide induces a (bulk) autophagy-dependent type of cell death that could be inhibited with antagonists of Na(+), K(+)-ATPase and the authors termed this type of cell death as "autosis" [20].…”
Section: Autophagy In Cell Survival and Cell Deathmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the most convincing observations of ACD have been made using lower model organisms like Caenorhabditis elegans, Drosophila melanogaster, and Dyctiostelium discoideum [5,[11][12][13], numerous studies have also demonstrated bona fide ACD in mammalian cells [14][15][16][17][18][19]. Liu et al observed that a cell-permeable Tat-Beclin 1 peptide induces a (bulk) autophagy-dependent type of cell death that could be inhibited with antagonists of Na(+), K(+)-ATPase and the authors termed this type of cell death as "autosis" [20].…”
Section: Autophagy In Cell Survival and Cell Deathmentioning
confidence: 99%
“…Other groups showed that downregulation of the AKT1/mTOR-axis using the histone deacetylase inhibitor suberoylanilide hydroxamic acid (SAHA) induced ACD in hepatocellular carcinoma (HCC) cell lines [55]. Finally, the cholesterol metabolite dendrogenin A (DDA) induced lethal autophagy, reminiscent of ACD, in myeloma and acute myeloid leukemia in vitro and in vivo [19].…”
Section: Pro-death Autophagymentioning
confidence: 99%
“…It includes three isoforms of LC3A, LC3B, LC3C, of which LC3B is associated with autophagy levels (Wu et al 2014a). LC3 has been reported in several tumors (including ovarian cancer (Shen et al 2008), brain cancer (Ghavami et al 2014), colorectal cancer (Wu et al 2015), prostate cancer (Zhang et al 2017), breast cancer (Jiang et al 2017), melanoma (Segala et al 2017). A meta-analysis of LC3 and ovarian cancer has shown that LC3 expression is associated with FIGO stage (Zhao et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In the case of melanoma cells treated with THPN, a chemical compound targeting NR4A1, cell death occurs after induction of excessive mitophagy, due to NR4A1 translocation to the inner membrane of the mitochondria, causing dissipation of mitochondrial membrane potential by the permeability pore complex ANT1/VDAC [14]. Furthermore, Dendrogenin A, a mammalian cholesterol metabolite ligand of liver-X-receptors (LCRs) induces Nr4a1 expression in association with excessive autophagic cell death both in vitro and in vivo [15,16], displaying anticancer and chemopreventive properties in mice [17]. Interestingly, NR4A1 interaction with anti-apoptotic BCL2 family members outside the BH3 domain induces autophagic cell death [18], which seems to be mediated by releasing BECN1 in a model of cigarette smokeinduced autophagic cell death [19].…”
Section: Introductionmentioning
confidence: 99%